Endocrine disruptive effects of polychlorinated biphenyls on the thyroid gland in female rats - Kilic, N; Sandal, S; Colakoglu, N; Kutlu, S; Seyran, A; Yilmaz, B (Tohoku Univ Medical Press, 2005)
KILIC, N., SANDAL, S., COLAKOGLU, N., KUTLU, S., SEYRAN, A. and YILMAZ, B. Endocrine Disruptive Effects of Polychlorinated Biphenyls on the Thyroid Gland in Female Rats. Tohoku J. Exp. Med., 2005, 206 (4), 327-332 - Polychlorinated biphenyls (PCBs) are persistent environmental pollutants. Aroclor 1221 (A1221) and Aroclor 1254 (A1254) are commercial PCB mixtures with low and high number of chlorination, respectively. We have comparatively investigated effects of A1221 and A1254 on serum levels of thyroid hormones and thyroid gland histology in adult female Wistar rats. Animals were subcutaneously injected with A1221 (10 mg/kg) or A1254 (10 mg/kg) for six weeks. One group of animals served as control. At the end, all animals were decapitated and trunk blood collected. Serum levels of triiodothyronine (T3) and thyroxine (T4) were measured by the electrochemiluminescence immunoassay method. Thyroid glands were removed for histopathological examination under light microscopy. Serum total T4 levels were significantly increased in A1221- and A1254-treated rats (P < 0.05). Serum free T4 levels were significantly increased in the A1254-treated rats (P < 0.01), but not in the A1221-treated rats. In contrast, the treatment with A1221 caused a significant increase in serum free T3 concentrations (p < 0.05) but not with A1254. Notably, either A1221 or A1254 caused distinct histopathological changes, such as formation of many microfollicles in the thyroid gland, which mimic the changes seen in thyrotoxicosis. In conclusion, both PCB mixtures induce toxic effects in the thyroid gland regardless of their degree of chlorination. We suggest that these environmental contaminants may disrupt thyroid hormone homeostasis in exposed individuals and thus pose a threat to human health. - PCBs; thyroxine; triiodothyronine; Aroclor and thyroid histology. (c) 2005 Tohoku University Medical Press.
Keywords: PCBs; thyroxine; triiodothyronine; aroclor and thyroid histology